The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/mde.3690
|View full text |Cite
|
Sign up to set email alerts
|

E‐commerce retail and reverse factoring: A newsvendor approach

Abstract: This study builds a theoretical model to examine how supply chain finance (SCF) services using fintech can ease e-commerce suppliers' capital constraints. Despite the innovation in the logistics industry during the Fourth Industrial Revolution and the increasing online shopping in the post-COVID era, small e-commerce enterprises may fail to grow owing to their budget constraints. Reverse factoring is believed to ease such suppliers' capital constraints. We analyze the effect of reverse factoring using the capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The ease of doing business is promoted and strongly related to digital business (Gupta 2022;Saidu et al 2022), especially for the Fintech industry, for which the literature shows that using such instruments can ease e-commerce suppliers' capital (Park and Ryu 2023). The hypothesis related to this indicator is:…”
Section: Millennials Generation Z and Market Growthmentioning
confidence: 99%
“…The ease of doing business is promoted and strongly related to digital business (Gupta 2022;Saidu et al 2022), especially for the Fintech industry, for which the literature shows that using such instruments can ease e-commerce suppliers' capital (Park and Ryu 2023). The hypothesis related to this indicator is:…”
Section: Millennials Generation Z and Market Growthmentioning
confidence: 99%
“…For instance, in the aviation industry, it was used to determine air cargo prices, as demonstrated by Shaban et al (2019). Similarly, Park & Ryu (2023) employed the model in e-commerce retailing to estimate the optimal quantity; however, they found that different decision-makers have different risk behaviours or preferences, which has been included in the traditional NV model. Schweitzer and Cachon (2000) showed this effect through an empirical study, highlighting that managers' decisions differ from the optimal solution resulting from the risk-neutral NV model.…”
Section: Traditional Newsvendor Modelmentioning
confidence: 99%